Study on Skin Separation in Date Fruits - Gophen, Moshe (Recent Progress in Plant and Soil Research Vol. 3, 2021)
The commercial disadvantage of skin separation in Date (Phoenix dactylifera) fruits is a worldwide concern. Barhee and Majhul are two varieties which produce skin separation. There are many Date varieties that do not produce skin separation. To investigate the phenomena of skin separation, two date varieties were compared: Dayri, which has no skin separation, and Barhee,which has significant skin separation. The study focuses on the mechanical qualities of the fruit's skin as well as its anatomical trait. The skin of Barhee fruits was discovered to be less flexible and more rigid, resisting artificial stretching force and tending to form folders while disconnecting from inner soft tissue, whereas the skin of Dairy fruits has the opposite features. The sequential linearity of the epidermal cells in Barhee and circular order in Dairy is one of the causes for this feature. The end finding of substantial skin separation in Barhee and zero in Dayri is supported by more differences in skin attributes. The agro-mechanical procedures of irrigation, nutritional regime and fruit management while on tree are of secondary importance in the case presented here.